Kilimanjaro: A Case of Meaningful Adventure And Service Learning Abroad - Cavanaugh, Cathy; Gajer, Ewa; Mayberry, John; O’Connor, Brendan; Hargis, Jace (Journal of International Students, 2015)
This qualitative evaluation explored how female undergraduate students developed an understanding of themselves and the broader world as a result of an adventure and service learning experience in Tanzania, Africa. The project built upon theoretical frameworks regarding meaningful learning—active, constructive, intentional, and authentic—and applied activity theory as a framework for interpreting outcomes. The study included multi-faceted examination of student perceptions of the effects of the year-long experience that culminated in a ten day trip to Tanzania, including a climb to the summit of Mount Kilimanjaro. Students’ reflections on the impacts of the trip focused on wanting, doing, reflecting, and relating. Thus, the experience catalyzed change in students’ understanding of the world that strongly indicates a meaningful learning experience.